The Profile of Secondary Glaucoma in China: A Study of Over 10, 000 Patients. Issue 10 (October 2021) - Gong, Haijun; Ren, Jiawei; Zheng, Bingru; Huang, Xiuyi; Liao, Yunru; Zhou, Yuying; Lin, Mingkai
Abstract : Background: Few studies have investigated the epidemiology of secondary glaucoma (SG) in China. This study analyzed the current profile of admitted patients with SG at the largest ophthalmic center in China. Methods: SG cases were retrieved retrospectively by International Classification of Disease-10 clinical coding data from January 2010 to December 2019. Demographic data, etiologies, and the management of SG were analyzed. The ratios of the etiologies were compared with previously reported data from other regions. The etiologies and management between the 2010 to 2014 group and the 2015 to 2019 group were compared. Results: A total of 11, 730 cases were enrolled. The mean age of the patients with SG was 44.45±19.45 years old. Men (66.94%) were more vulnerable than women (33.06%). The etiologies of SG in 2010 to 2019 were trauma (28%), vascular disease (18%), lens-induced (9%), inflammation (11%), drug-induced (2%), anterior segment surgery (7%), posterior segment surgery (11%), syndrome-associated (4%), and tumors (1%). Compared with other regions, our data have a higher proportion of trauma and vascular disease-associated SG. Compared with 2010 to 2014, trauma-induced SG declined, and drug-induced SG, anterior segment surgery, and syndrome-associated SG increased in 2015 to 2019 ( P <0.001). Vascular disease-associated SG cases were older than trauma-induced SCs and had a higher percentage in retired patients ( P <0.001), whereas trauma-induced SGs were more prevalent in pediatric patients than vascular disease-related SGs ( P <0.001). In addition, the application of drainage device implantation, cataract surgery, and cyclophotocoagulation increased, whereas trabeculectomy and anterior chamber paracentesis and cyclocryotherapy decreased in 2015 to 2019 ( P <0.005). Conclusion: Although the etiology spectrum has changed during the last 10 years, trauma and vascular disease are still common causes of SG in southern China. Traditional antiglaucoma surgery decreased gradually, and more advanced treatments emerged for its treatment. Up-to-date knowledge of SGs reflects the impact of economic development and ophthalmic service improvement on SGs and is of great value for ophthalmologists to detect SGs early and manage them in a timely manner. Abstract : Supplemental Digital Content is available in the text.